The Juvenile Collection in the Academic Library. - Crosetto, Alice; Horan, Mark (International Journal of the Book, 2007)
Individuals on a college campus are often puzzled, maybe indignant, about juvenile literature being in their academic library. But 59% of Ohio academic libraries have identifiable juvenile literature collections while another 22% have juvenile literature, including picture books and big books, in their main collections. Why the dismay when academics discover The Very Hungry Caterpillar shares shelf space with the Oxford Dictionary of Astronomy? The question of the Juvenile Collection in an academic library mirrors the same asked regarding Children's Literature in higher education and its place in the canon of literature worthy of academic discussion. A review of Library Literature reveals very little research in this topic. Education students and faculty are not the only ones on the college campus that utilize this collection; other programs that use this collection are: art therapy, art, clinical and developmental psychology, language and linguistics, cultural anthropology, foreign languages, religions, and interdisciplinary programs focusing on multicultural and diversity studies. In financially challenged times, escalating costs of print materials and electronic resources make this an easily targeted collection - a collection of books that many say should stay in the public and school library. Maintaining a Juvenile Collection does provide some challenges: • Limited funds allocated for this budget line creates the need to be most selective in acquiring titles, almost guaranteeing a quality collection; • Is the Juvenile Collection a working or a historical collection? • Pathfinders need to be designed to advertise the Collection to both Education and non-Education students. This paper will address the challenges and importance of maintaining a juvenile collection in an academic library. Does juvenile literature belong in the academic library? How can the academic librarian provide support for juvenile literature? These questions will initiate further discussion.